Clinical-cognitive Characterization of Spinocerebellar Ataxia Type 2 - Alberto Caballero Laguna; Luis Velázquez Pérez; Alián Pérez Marrero (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: spinocerebellar ataxia type 2 is a genetic disease with an autosomal dominant inheritance pattern. It constitutes a health problem for Cuba, especially for the Holguín province, which concentrates the largest sick and at-risk population that has been reported worldwide so far. Objective: to characterize from the clinical and cognitive point of view patients with spinocerebellar ataxia type 2 diagnosed during the years 2018 and 2019. Methods: a retrospective study was carried out in 28 patients with type 2 spinocerebellar ataxia diagnosed at the Holguín Clinic for Research and Rehabilitation of Hereditary Ataxias, which also allowed them to be correlated over time. The sample consisted of 28 patients with a mild stage of the disease to which the Scale for the Assessment and Rating of Ataxia and Montreal Cognitive Assessment Scale were applied to evaluate the progression of the disease from the clinical and cognitive point of view, respectively, with a difference of one year between the two samplings. Results: the mean age of the patients was 50.3 years with a slight predominance of the female sex, the average evolution time was 9.82 years, being longer for the female sex. The mean age of the disease start was 39.54 years. Conclusions: between the two evaluations there was a progression of cerebellar manifestations and a deterioration of cognitive functions was evidenced, giving an important role to the cerebellum in both functions by this study.